The spatial distribution of sedimentary compounds and their environmental implications in surface sediments of Lake Khar Nuur (Mongolian Altai). Issue 3 (26th January 2021) - Strobel, P.; Struck, J.; Zech, R.; Bliedtner, M.
Abstract: Lake sediments are valuable natural archives to reconstruct paleoclimate and paleoenvironmental changes which consist of inorganic and organic sediment compounds of allochthonous origin from the catchment and of autochthonous production in the lake. However, for robust paleo‐reconstructions it is important to develop a better understanding about sedimentation processes, the origin of inorganic and organic sediment compounds and their distribution within the lake. In this context, modern process studies provide important insights, although environmental and anthropological changes can affect the spatial distribution of sediment compounds through time. Therefore, in this study the spatial distribution of grain size and geochemical proxies in 52 surface sediment samples from Lake Khar Nuur, a small high‐altitude lake in the Mongolian Altai with a small and anthropogenically used hydrological catchment, is investigated. The results show a distinct sediment focussing in the two deep basins of the lake, which therefore act as accumulation zones. In those accumulation zones, total organic carbon (TOC), total nitrogen (N) and their isotopic composition (δ 13 CTOC, δ 15 N) as well as n ‐alkanes indicate that organic sediment compounds are a mixture of both allochthonous and autochthonous origin. While the recent catchment vegetation consists of grasses/herbs and the shrub Betula nana (L.) with distinct differences in their n ‐alkane homologue patterns, those differences are not reflected in the sediment surface samples which rather indicates that grass‐derived n ‐alkanes become preferentially incorporated in the lake. Extensive anthropogenic activity such as grazing and housing in the southern part of the catchment causes soil erosion which is well reflected by high TOC, N and sulphur (S) contents and 15 N depleted δ 15 N values at the central southern shore, i.e. increased allochthonous sediment input by anthropogenically‐induced soil erosion. Overall, the surface sediments of Lake Khar Nuur origin from allochthonous and autochthonous sources and are focussed in the accumulation zones of the lake, while their distribution is both environmentally and anthropogenically driven. Abstract : Surface sediments of lake Khar Nuur show highest transport energies at the shore lines and point to sediment accumulation of terrestrial and aquatic compounds in the deepest parts. Anthropogenic activity and soil erosion in the catchment are suggested by enhanced terrestrial input.